Biomonitoring chromium III or VI soluble pollution by moss chlorophyll fluorescence. (March 2018) - Chen, Yang-Er; Mao, Hao-Tian; Ma, Jie; Wu, Nan; Zhang, Chao-Ming; Su, Yan-Qiu; Zhang, Zhong-Wei; Yuan, Ming; Zhang, Huai-Yu; Zeng, Xian-Yin; Yuan, Shu
Abstract: We systematically compared the impacts of four Cr salts (chromic chloride, chromic nitrate, potassium chromate and potassium bichromate) on physiological parameters and chlorophyll fluorescence in indigenous moss Taxiphyllum taxirameum . Among the four Cr salts, K2 Cr2 O7 treatment resulted in the most significant decrease in photosynthetic efficiency and antioxidant enzymes, increase in reactive oxygen species (ROS), and obvious cell death. Different form the higher plants, although hexavalent Cr(VI) salt treatments resulted in higher accumulation levels of Cr and were more toxic than Cr(III) salts, Cr(III) also induced significant changes in moss physiological parameters and chlorophyll fluorescence. Our results showed that Cr(III) and Cr(VI) could be monitored distinguishably according to the non-photochemical quenching (NPQ) fluorescence of sporadic purple and sporadic lavender images respectively. Then, the valence states and concentrations of Cr contaminations could be evaluated according to the image of maximum efficiency of PSII photochemistry (Fv/Fm) and the quantum yield of PSII electron transport (ΦPSII). Therefore, this study provides new ideas of moss's sensibility to Cr(III) and a new method to monitor Chromium contaminations rapidly and non-invasively in water. Graphical abstract: Highlights: Among four Cr salts, K2 Cr2 O7 had the highest toxic effects on mosses. The high toxicity of Cr(VI) was mainly due to its uptake and the synergetic effect with heavy metal ions. Cr(III) and Cr(VI) may be distinguished firstly according to the image of NPQ. The valence states and concentrations of Cr may be evaluated according to Fv/Fm and ΦPSII.